2008
DOI: 10.1002/jgm.1156
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term effect of gene therapy for chronic ischemic myocardium using platelet‐derived endothelial cell growth factor in dogs

Abstract: We conclude that gene targeting of ischemic myocardium using PD-ECGF generated long-term improvement in cardiac function by causing angiogenesis, arteriogenesis and inhibiting apoptosis, but did not induce neoplasms in the remote organs, and may be a promising therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 26 publications
0
12
0
1
Order By: Relevance
“…12,13,33 In our previous study, we demonstrated the therapeutic effects of PD-ECGF/TP gene transfer on ischemia by promoting angiogenesis and inhibiting apoptosis (summary in Fig 5). [27][28][29] Sengupta et al 33 have reported that equimolar concentrations of PD-ECGF/TP induce a similar total monolayer recovery of wounded endothelium in vitro as well as vascular endothelial growth factor, strongly suggesting the chemotaxis functional effect of PD-ECGF/TP on endothelium. Therefore, as shown in Fig 5, we speculate that in addition to the suppressive effect of PD-ECGF/TP on VSMCs, PD-ECGF/TP itself, its enzymatic substrates, or PD-ECGF/TP-derived HO-1 expression may promote endothelial cell proliferation and protect endothelial cells from injury.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…12,13,33 In our previous study, we demonstrated the therapeutic effects of PD-ECGF/TP gene transfer on ischemia by promoting angiogenesis and inhibiting apoptosis (summary in Fig 5). [27][28][29] Sengupta et al 33 have reported that equimolar concentrations of PD-ECGF/TP induce a similar total monolayer recovery of wounded endothelium in vitro as well as vascular endothelial growth factor, strongly suggesting the chemotaxis functional effect of PD-ECGF/TP on endothelium. Therefore, as shown in Fig 5, we speculate that in addition to the suppressive effect of PD-ECGF/TP on VSMCs, PD-ECGF/TP itself, its enzymatic substrates, or PD-ECGF/TP-derived HO-1 expression may promote endothelial cell proliferation and protect endothelial cells from injury.…”
Section: Discussionmentioning
confidence: 93%
“…15,[27][28][29] We used gene transfection of human PD-ECGF/TP into rat VSMCs to study the mechanism of inhibitory effect of PD-ECGF/TP on VSMC, and found that inhibition of VSMC proliferation was correlated with the upregulation of p27 KIP1 and HO-1. 15 We also found that adventitial gene transfer of TP/PD-ECGF in a balloon injury rat carotid artery model markedly inhibited the intimal hyperplasia.…”
Section: Discussionmentioning
confidence: 99%
“…268 This experimental gene therapy also proved to have a longterm beneficial effect in the treatment of chronic ischemic myocardium. 269 As VSMC play an important role in vessel maturation during angiogenesis, and deregulated growth or motility of VSMC contributes to the pathogenesis of vascular obstructive diseases (such as ischemia), the effect of TP on VSMC migration and proliferation was investigated. TP-overexpressing VSMC migrated and proliferated more slowly than mocktransfected VSMC.…”
Section: Tp Induces the Expression And/or Secretion Of Other Angiogenmentioning
confidence: 99%
“…We have found that direct injection of a plasmid vector encoding human TYMP into ischemic canine myocardium or rabbit hindlimb promotes angiogenesis in cardiac and skeletal muscle 5,9,10 and improves myocardial function and prevents hindlimb necrosis. We also found that TYMP inhibited vascular smooth muscle cell (VSMC) proliferation and migration 1113 .…”
Section: Introductionmentioning
confidence: 98%